Analisis Penyebab Kerusakan Transmisi Dump Truck LGMG CMT 96 DT 060-032 di PT ANSAF INTI RESOURCES - Irsal Revanza; Surojo, Surojo; Harjono, Harjono; Prihadianto, Braam Delfian (Jurnal Teknologi dan Rekayasa Alat Berat, 2025)
Dump truck LGMG CMT 96 is employed by PT Ansaf Inti Resources for overburden transportation, operating up to 22 hours per day. In the unit coded DT 060-032, a transmission failure was detected at 2,143.5 hours, significantly below the company's target of 20,000 hours. The symptoms of the failure included the activation of the transmission warning indicator, fault codes, excessive jolts during operation, transmission overheating, and gear shifting failures. This study identifies the primary causes of the failure through monitor checks, visual inspections, historical maintenance data, the Machine Inspection Program (PPM), the Lubricant Analysis Program (PAP), and transmission overhaul results. The applied failure analysis method revealed brittle fracture of the lock-up clutch and excessive clutch wear due to deformation, heat spots, and blue temper. Operational errors were concluded to be the main cause of the transmission failure, leading to clutch slip and the appearance of fault code F:191 S:8.